Diversity, distribution and ecology of benthic molluscan communities on the Portuguese continental shelf - Martins, R. (2018)
The diversity, ecology and distribution patterns of the Portuguese continental shelf malacofauna and its relationship with abiotic factors were studied from samples covering the western and the southern coast. A total of 2544 specimens were identified corresponding to 169 taxa, mostly bivalves (62% of the total taxa). Abra alba was the most abundant and the most frequent species. The alpha diversity ranged from one species to 21 spp. 0.1m-2. The highest abundance and diversity were obtained in coarser sediments. Multivariate analysis based on the abundance data identified five major malacological groups: (a) Angulus pygmaeus and Thracia villosiuscula in the coarser sediments of the western inner and mid shelf; (b) Calyptraea chinensis and Leptochiton cancellatus in the heterogeneous and organically enriched sediments of the southern shelf; (c) Angulus fabula, Spisula subtruncata and Pharus legumen in the near shore exposed fine sands; (d) A. alba in muddy fine sands, mainly in the northwestern shelf and (e) Saccella commutata in the southwestern deeper shelf. The malacofauna could be used as a proxy for the major benthic communities known to occur in this area, except in muddy patches, where molluscs were absent or low abundant. Median grain-size, gravel content, depth and hydrodynamic regime were the environmental factors best related to the malacofauna spatial distribution patterns. This study sets the first record of Astarte borealis, Leptochiton asellus, Mercenaria mercenaria and Montacuta phascolionis in the Portuguese shelf and the most northern limit for Anadara polii, Glycymeris nummaria, and Leptochiton algesirensis along the northwestern shelf. This study also gives new ecological insights for several species, in terms of bathymetric range distribution, as well as habitat type and highlighted the transitional characteristics of the molluscan communities from this particular northeastern Atlantic area where boreal, temperate and subtropical faunas can coexist.